Other people's houses - Mackintosh, Clare (Sourcebooks, 2025)
"You want what they have, but what price would you pay? The Hill is the kind of place everyone wants to live: luxurious, exclusive and safe. But now someone is breaking and entering these Cheshire homes one by one, and DS Leo Brady suspects the burglar is looking for something, or someone, in particular. Over the border in Wales, DC Ffion Morgan recovers the body of an estate agent from the lake. There's no love lost between Ffion and estate agents, but who hated this one enough to want her dead - and why? As their cases collide, Ffion and Leo discover people will pay a high price to keep their secrets behind closed doors . . ." --